The role of the experiences with the dead in the lives of individuals in rural Slovakia - Uhrin, Michal (Anthropological notebooks, 2025)
This paper aims to explore people’s experiences with the dead and subsequent rituals, practices and associated ideas. Experiences and subsequent practices can be analyzed and classified according to whether they are individual or collective, according to their degree of generality, intentionality and rigidity; and in terms of whether they are first-hand experiences or general narratives.The data presented in the paper were gathered during long-term ethnographic research carried out in the Horehronie region in central Slovakia in 2023 and 2024. The research site is characterized by a high prevalence of members of the Roman Catholic Church who are of Slovak nationality. The ethnographic research carried out so far shows that rituals, practices, associated ideas, and people’s experiences with the dead and their agency are multidimensional phenomena influ-enced mainly by the Catholic religion, and to a lesser extent by folk religion or vernacu-lar religion. The agency of the dead is usually manifested because of experiences with the dead that cause the performance of rituals, ritualized types of behavior, ritualized practices or other activities, and because of contemplation about the moral and religious aspects of the lives of individuals and society.
Keywords: agency of the dead; cultural anthropology; death; delovanje mrtvih; ethnography; ethnology; etnografija; etnologija; experiences with the dead; izkušnje z mrtvimi; kulturna antropologija; mrtvi; pracrice; praksa; ritual; rituali; Slovakia; Slovaška; smrt; vloga mrtvih